1998
DOI: 10.1097/00004836-199804000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic Recidivism After Liver Transplantation for Alcoholic Cirrhosis

Abstract: Liver transplantation (LT) for alcoholic cirrhosis remains controversial. This controversy surrounding LT in alcoholics focuses on the risk of alcohol recidivism and on potential noncompliance with the immunosuppressive regimen, both of which result in graft failure. Our study examined alcohol recidivism after LT by measuring alcohol in urine and its repercussion on the allograft. Forty-four consecutive alcoholic patients and a comparison group of 17 patients receiving LT were included in this study and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 18 publications
2
27
0
2
Order By: Relevance
“…Poor post-OLT outcome has previously been noted in actively drinking patients (13). However, other studies have found no effect on graft and patient survival, nor compliance with immunosuppression despite recidivism rates estimated at 25% (14) and 32% (15), respectively. Reports of renal transplantation in former drug addicts have not shown a poor outcome; however, recidivism was not rigorously investigated in these studies (16).…”
Section: Discussionmentioning
confidence: 89%
“…Poor post-OLT outcome has previously been noted in actively drinking patients (13). However, other studies have found no effect on graft and patient survival, nor compliance with immunosuppression despite recidivism rates estimated at 25% (14) and 32% (15), respectively. Reports of renal transplantation in former drug addicts have not shown a poor outcome; however, recidivism was not rigorously investigated in these studies (16).…”
Section: Discussionmentioning
confidence: 89%
“…There is a relatively low incidence of recidivism in short-term periods of follow-up [9][10][11] ; however, more recent studies suggested that recidivism rates increase with longer followup. 17,18 In a preliminary study, we found that 48% of the patients with ALD admitted consuming any alcohol after transplantation, although a return to heavy drinking (Ͼ20 units/wk) was reported in only 15%. The majority returned to drinking within 1 year.…”
mentioning
confidence: 88%
“…9,[11][12][13][14][15][16] These patients may return to a pattern of alcohol consumption that poten-tially damages the transplanted liver, as well as affects compliance with the immunosuppressive regimen and follow-up appointments, which may put the graft at risk. 2,17 Reported rates of recidivism vary between 0% and 95% 1,3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] ; in part, this discrepancy can be attributed to the definition of recidivism used. There is a relatively low incidence of recidivism in short-term periods of follow-up [9][10][11] ; however, more recent studies suggested that recidivism rates increase with longer followup.…”
mentioning
confidence: 99%
“…O principal argumento utilizado era a grande probabilidade de que índices elevados de recidiva diminuíssem a sobrevida, quer pelo desenvolvimento de lesões graves no enxerto associadas ao etanol, quer por outros problemas médicos com uso inadequado de imunossupressores ou complicações associadas ao alcoolismo crônico. Muitos estudos a respeito da recidiva de consumo de álcool após o transplante hepático têm sido publicados na última década (7,10,14,15,17,23,25,28,32) . A maioria dos trabalhos demonstra taxas de recidiva ao redor de 12% a 50% (4,5,6,10,11,12,13,14,15,20,28) .…”
Section: Discussionunclassified
“…Muitos trabalhos têm mostrado resultados semelhantes (10,28) . Segundo MALDONADO e KEEFFE (23) , a maioria dos centros transplantadores ainda acredita que são necessários 6 meses de abstinência pré-transplante.…”
Section: Discussionunclassified